St Clare of Assisi and the Poor Clares: a new spring - Gerrard, Paul M. (Studies in church history, 1997)
The Second Vatican Council (1962-5) called for religious orders to renew themselves in a two-fold return to the sources of their Christian life, jointly to the Gospels and to the inspiration of each institute’s founder, a process to be combined with a movement to bring the religious life into line with the ‘tenor of the times’.Thirty years after the issuing on 28 October 1965 of Perfectae Caritatis, the conciliar decree on the religious life, it seems particularly relevant to look at how far this renewal has been enacted since the Council. Furthermore, given the theme of this volume it seems especially apt to examine the role which that call for the rediscovery of the founder’s spirit has played in one such renewal.